Trophoblast-uterine interactions at implantation - Aplin John D; Kimber Susan J (BMC, 2004)
Abstract Implantation of the embryo in the uterus is a critical and complex event and its failure is widely considered an impediment to improved success in assisted reproduction. Depending on whether placentation is invasive or superficial (epitheliochorial), the embryo may interact transiently or undergo a prolonged adhesive interaction with the uterine epithelium. Numerous candidate interactions have been identified, and there is good progress on identifying gene networks required for early placentation. However no molecular mechanisms for the epithelial phase are yet firmly established in any species. It is noteworthy that gene ablation in mice has so far failed to identify obligatory initial molecular events.